Consumer Psychosocial Motivations: An affect the Online Shopping Behavior is to decide to buy online throughout the World - TalluriSreekrishna; RAO CHILKA, KOTESWARA (International Journal of Psychosocial Rehabilitation, 2024)
Recent Psychosocial motos are shown an interest in investigating consumer motivations that affect online shopping behaviour. It is yet to understand what factors influence the online shopping decision process. The objective of this study is to provide an overview of the online shopping decision process by comparing the offline and online decision making and identifying the factors that motivate online customers to decide or not to decide to buy online. It is found that the marketing communication process differs between offline and online consumer decision. Managerial implications are developed for online stores to improve their website.